Motility and Biofilm of Ralstonia syzygii subsp. celebesensis, the Causative Agent of Banana Blood Disease - Saraswati, Vivian Thea; Subandiyah, Siti; McCann, Honour C.; Joko, Tri (Universitas Gadjah Mada, 2025)
Blood disease in bananas is caused by Ralstonia syzygii subsp. celebesensis. This disease is a significant phytopathological concern, leading to deterioration of the plant's xylem tissue. Symptoms observed in infected plants typically begin from the shoot and banana inflorescence and progressively spread to other parts of the plant. The spread of these symptoms may result from the motility of R. syzygii subsp. celebesensis within the vascular system. This study aims to investigate the bacterial motility and biofilm formation ability, both contributing to the blockage of water and nutrient flow in the plant. The research methods included bacterial cultivation, molecular detection, motility assays (swimming and swarming tests), as well as biofilm and pellicle formation assay. The results indicated that R. syzygii subsp. celebesensis exhibited sliding motility but did not demonstrate swarming ability. Additionally, the bacterium was capable of forming both biofilm structures and pellicle layers. These findings provide insights into the role of motility types and colony structure formation in the virulence of R. syzygii subsp. celebesensis, potentially influencing the infection process in banana plants. Furthermore, this study's results are expected to contribute to developing improved disease management strategies.